Diving in the Arctic: Cold Water Immersion’s Effects on Heart Rate Variability in Navy Divers - Lundell, Richard V.; Räisänen-Sokolowski, Anne K.; Wuorimaa, Tomi K.; Ojanen, Tommi; Parkkola, Kai I. (Frontiers in Physiology, 2020)
Introduction: Diving close to the Arctic circle means diving in cold water independent of the time of year. The human body reacts to cold through autonomous nervous system (ANS) mediated thermoregulatory mechanisms. Diving also induces ANS responses as a result of the diving reflex. Materials and Methods: In order to study ANS responses during diving in Arctic water temperatures, we retrospectively analyzed repeated 5 min heart rate variability (HRV) measures and mean body temperature from dives at regular naval diving equipment measurement tests in 0 °C water. Three divers performed seven dives without physical activity (81 – 91 min), and two divers performed four dives with physical activity after 10 min of diving (0 – 10 min HRV recordings included in the study). Results: Our study showed a significant increase in parasympathetic activity (PNS) at the beginning of the dives, after which PNS activity decreased significantly (measure 5 – 10 min). Subsequent measurements (15 – 20 min and onwards) showed a significant increase in PNS activity over time. Conclusions: Our results suggest that the first PNS responses of the human diving reflex decrease quickly. Adverse effects of PNS activity should be considered on long and cold dives. To avoid concurrent sympathetic (SNS) and PNS activity at the beginning of dives, which in turn may increase the risk for arrhythmia in cold water, we suggest a short adaptation phase before physical activity. Moreover, we suggest it is prudent to give special attention to cardiovascular risk factors during pre-dive examinations for cold water divers.